RELATIONSHIP OF STRENGTH MUSCLE STRENGTH TO DRIBBLING SKILLS IN FUTSAL GAMES IN SMK NEGERI 03 KAUR - Edwin Apriansyah; Febby Erla Perdima; Satria Agustian Lesmana (Perkumpulan Dosen Muda Bengkulu, 2020)
Based on the observations of researchers on the implementation of Activities in SMK Negeri 03 Kaur, that the dribbling skills of athletes are not good so that it often causes the ball to get out of control. This problem is thought to be caused by several factors, including the low level of leg muscle strength of students. This study aims to determine the relationship between leg muscle strength and dribbling skills. This research method is a correlational method. The population of this research is all 22 SMK Negeri 03 Kaur players as samples taken in total sampling, the place of research in the field of SMK Negeri 03 Kaur, while the research time is April 2019. Leg muscle strength data is taken by vertical jump test, and Dribbling Ability data taken with the Dribbling test. The data analysis technique of this research uses correlation analysis techniques. The results of the data analysis show that: There is a significant relationship between leg muscle strength (X) and dribbling skills in students of State Vocational School 03 Kaur, with a value of rxy = 0.96 r (0.05) (22) = 0.423.